Acoustic scattering by cylindrical scatterers comprising isotropic fluid and orthotropic elastic layers - Bao, Chunyan (Kansas State University, 2016)
Acoustic scattering by a cylindrical scatterer comprising isotropic acoustic and orthotropic elastic layers is theoretically solved. The orthotropic material is used for the scattering problem because the sound speeds along radial and tangential axes can be different; which is an important property for acoustic cloaking design. A computational system is built for verifying the solutions and conducting simulations. Scattering solutions are obtained based on two theoretical developments. The first one is exact solutions for elastic waves in cylindrically orthotropic elastic media, which are solved using Frobenius method. The second theoretical development is a set of two canonical problems for acoustic-orthotropic-acoustic media. Based on the two theoretical developments, scattering by three specially selected simple multilayer scatterers are analyzed via multiple-scattering approach. Solutions for the three scatterers are then used for solving a “general” multilayer scatterer through a recursive solution procedure. The word “general” means the scatterer can have an arbitrary number of layers and each layer can be either isotropic acoustic or orthotropic elastic. No approximations have been used in the process. The resulting analytically-exact solutions are implemented and verified. As an application example, acoustic scattering by a scatterer with a single orthotropic layer is presented. The effects on the scattering due to changing parameters of the orthotropic layer are studied. Acoustic scattering by a specially designed multilayer scatterer is also numerically simulated. Ratios of the sound speeds of the orthotropic layers along r and θ directions are defined to satisfy the requirement of the Cummer-Schurig cloaking design. The simulations demonstrate that both the formalism and the computational implementation of the scattering solutions are correct.
Keywords: Acoustic scattering; Cylindrical scatterer; Conventional orthotropic elastic; Conventional isotropic fluid; Acoustic cloaking; Optimization